Management of Obstetric Perineal Tears: Do Obstetrics and Gynaecology Residents Receive Adequate Training? Results of an Anonymous Survey - A. Cornet; O. Porta; L. Piñeiro; E. Ferriols; I. Gich; J. Calaf (Obstetrics and Gynecology International)
Background/Aim. To evaluate the obstetrics and gynaecology residents' perspective of their training and experience in the management of perineal tears that occur during assisted vaginal delivery. We hypothesised that residents would perceive room for improvement in their knowledge of pelvic floor anatomy and the training received in tears repair. Design. Descriptive cross-sectional study. Population/Setting. Seventy-two major residents from all teaching hospitals in Catalonia. Methods. A questionnaire was designed to evaluate experience, perception of the training and supervision provided. Results. The questionnaire was sent to all residents (𝑛=72), receiving 46 responses (64%). The participants represented 15 out of the 16 teaching hospitals included in the study (94% of the hospitals represented). Approximately, 52% of residents were in their third year while 48% were in their fourth. The majority of them thought that their knowledge of pelvic floor anatomy was poor (62%), although 98% felt confident that they would know when an episiotomy was correctly indicated. The survey found that they lacked experience in the repair of major degree tears (70% had repaired fewer than ten), and most did not carry out followup procedures. Conclusion. The majority of them indicated that more training in this specific area is necessary (98%).